The Use of Dog Sledges during the British Search for the Missing Franklin Expedition in the North American Arctic Islands, 1848–59 - Barr, William (ARCTIC, 2009)
While the bulk of the searching parties sent out from the British ships deployed on the search for the missing Franklin expedition in the North American Arctic Islands over the period 1848–59 employed man-hauled sledges, dog sledges were also used quite extensively. The dog sledges were especially (but not exclusively) used as “couriers,” that is, for communication between the various wintering ships, where speed was the primary requirement. The total distance covered by dog sledges (excluding short hauls in the vicinity of the wintering ships) was, at a minimum, 11 576 km; this distance compares with the minimum 41 555 km covered by man-hauled sledges. Bien que la plupart des équipes de recherche déployées par les navires britanniques à la recherche de l’expédition de Franklin disparue dans l’archipel Arctique nord-américain pendant la période de 1848–1859 se soient servi de traîneaux tirés par des humains, elles ont également employé des traîneaux à chiens à maintes reprises. Les traîneaux à chiens servaient plus particulièrement (mais non pas exclusivement) de « messagers » en ce sens qu’ils établissaient les liens de communication entre les divers navires en hivernage, la rapidité de transmission étant essentielle. La distance totale à avoir été parcourue par les traîneaux à chiens (ce qui ne comprend pas les courtes distances dans la région des navires en hivernage) s’est chiffrée, au minimum, à 11 576 kilomètres, comparativement à la distance minimale de 41 555 kilomètres parcourue par les traîneaux tirés par des humains.